Placental nutrient and transport system in fetus with small for gestational age and growth restriction compared to appropriate for gestational age - Wibawa, Aria; Wibowo, Noroyono; Timan, Ina Susianti; Rohsiswatmo, Rinawati; Putri, Atikah Sayogo (Medical Journal of Indonesia, 2024)
BACKGROUND Fetal growth restriction (FGR) has multifactorial etiology, including nutrition. Fetal nutrient status depends not only on an adequate supply of key nutrients but also optimal delivery, served by the placenta as a major metabolic and transport organ. This study aimed to evaluate the status of placental oxygen and nutrient concentration and their transporters between appropriate for gestational age (AGA), small for gestational age (SGA), and FGR. METHODS This cross-sectional study was conducted at Cipto Mangunkusumo Hospital, Jakarta, from July 2018 to December 2020. Patients were divided into 3 groups, namely AGA, SGA, and FGR. The placental samples were taken following delivery. Placental concentration of glucose, amino acids (AAs), and fatty acids (FAs) were measured by calorimetric assay, liquid chromatography-tandem mass spectrometry, and gas chromatography-mass spectrometry, respectively. Placental concentration of vascular endothelial growth factor (VEGF), glucose transporter 1 (GLUT1), system y+L, and fatty acid transport protein 1 (FATP1) were examined using enzyme-linked immunosorbent assay. RESULTS A total of 57 subjects participated in the study. Compared with the AGA group, the SGA and FGR groups had lower placental AA concentration (p = 0.004), higher placental FA concentration (p = 0.048), higher placental expression of VEGF (p = 0.003), system y+L (p = 0.07), and FATP1 (p = 0.021). No difference in placental glucose and GLUT1 concentration was observed among all groups (p = 0.301). CONCLUSIONS The similar profile of macronutrient concentration with increased expression of oxygen and several nutrient transporters in SGA and FGR groups might indicate similar pathogenesis between these groups.